To purchase or lease: Investigating the finance decision of plug-in electric vehicle owners in California. (1st September 2022) - Hoogland, Kelly; Chakraborty, Debapriya; Hardman, Scott
Abstract: In this paper we explore the factors that influence plug-in electric vehicle (PEV) buyers' decision to lease or purchase a PEV. We estimate a binary logistic regression model using survey data of 9, 472 PEV owners in California, surveyed between 2015 and 2018. Several factors influencing the purchase versus lease decision are identified; battery electric vehicles (BEVs) are more likely to be leased over plug-in hybrid electric vehicles (PHEVs). Results show a positive association between electric range and likelihood of purchasing BEVs, but a negative association for PHEVs. Sociodemographic factors such as living in a single-family home, homeownership, and having at home solar panels are associated with purchasing. An increase in the stated importance of high occupancy vehicle/carpool lane access is associated with the decision to lease, but an increase in state rebate importance is associated with the decision to purchase. The results highlight different factors that influence the decision to purchase or lease a PEV, both of which will be important strategies for growing the PEV market.